Asymmetric information, dividend reductions, and contagion effects in bank stock returns - Bessler, Wolfgang; Nohel, Tom (Journal of Banking & Finance, 2000)
In an environment of asymmetric information, banks face information externalities due to their role as intermediaries of information. In particular, bank insiders will possess private information from monitoring loan customers. Accordingly, outsiders may interpret changes in a bank's financial policy as signals about the quality of its loan portfolio and to the extent that the assets (loans) of different banks are viewed as similar, they will interpret such signals as pertaining to non-announcing banks as well leading to contagion effects. We test for the presence of contagion effects in stock returns associated with announcements of dividend cuts by money-center banks. We find that dividend cuts induce negative abnormal returns in the stocks of non-announcing money-center banks and to a lesser extent in the stocks of large regional banks. The observed contagion effects appear consistent with informed rather than contagious panic behavior because these effects are systematically related to risks that are common to all affected banks.